ANALISIS FORMALIN DALAM SAMPEL IKAN TONGKOL MENGGUNAKAN FLUORAL-P SEBAGAI PENGOMPLEKS SECARA SPEKTROFOTOMETRI UV-VIS - Juli Manda Sari; Indang Dewata; Edi Nasra (Departemen Kimia FMIPA UNP, 2016)
Had been observed the research on the analysis of formaldehyde in samples of mackarel tuna using fluoral-p as complexing UV-Vis spectrophotometry. This study aims to obtain optimum conditions and validation of analytical methods and analyze the levels of formaldehyde in the mackarel tuna using fluoral-p as a complexing agent. The method used in this research that UV-Vis spectrophotometry, where formaldehyde is reacted with fluoral-p form compounds 3,5-diacetyl-1,4-dihidrolutidin (DDL) yellow and measured at a wavelength of 412 nm using a UV-Vis spectrophotometer. Phase optimization done of the effect of pH, complexing time and stability of the complex. While the validation phase methods of analysis undertaken include the manufacture calibration curve and linearity, LOD and LOQ, precision test and test accuracy. The results showed that the complex solution of formalin and fluoral-p optimum at pH 4 with a complexing for 75 minutes. Validation of the methods result in the regression equation Y = 0.022x + 0.013 with a correlation coefficient (r) = 0.0989, LOD value of 0.2 ppm and 0.6 ppm LOQ values, and average% recovery was 101.7%. Formaldehyde levels were obtained in samples mackarel tuna originating from the Pasar Lubuk Buaya and SPAR Supermarkets identified containing formaldehyde levels exceed a safe threshold is 6 ppm and 20 ppm.